Theology - Ford, David F.
This book offers a concise and original introduction to the whole of the theological discipline. Writing with a focus on Christianity, David Ford provides a trenchant and balanced discussion of the study of faith and religion. He describes the development of the field of theology, and explores such issues as knowledge, community, worship, salvation, God, prayer, and evil. Ford also weaves the idea of the quest for wisdom into the entire fabric of his discussion, and concludes with a look ahead to the theology of the next century. Theology: A Very Short Introduction tackles the questions raised by and about religion in a thought-provoking and engaging manner